Coral biodiversity and bio-construction in the northern sector of the mesoamerican reef system - Rodríguez-Zaragoza, Fabián A.; Arias-González, Jesús E. (Frontiers in Marine Science, 2015)
As the impact of anthropogenic activity and climate change continue to accelerate rates of degradation on Caribbean coral reefs, conservation and restoration faces greater challenges. At at this stage, of particular importance in coral reefs, is to recognize and to understand the structural spatial patterns of benthic assemblages. We developed a field-based framework of a Caribbean reefscape benthic structure by using hermatypic corals as an indicator group of global biodiversity and bio-construction patterns in eleven reefs of the northern sector of the Mesoamerican Barrier Reef System (nsMBRS). Four hundred and seventy four video-transects (50 m long by 0.4 m wide) were performed throughout a gradient of reef complexity from north to south (∼400 km) to identify coral species, families and ensembles of corals. Composition and abundance of species, families and ensembles showed differences among reefs. In the northern zone, the reefs had shallow, partial reef developments with low diversities, dominated by Acropora palmata, Siderastrea spp., Pseudodiploria strigosa and Agaricia tenuifolia. In the central and southern zones, reefs presented extensive developments, high habitat heterogeneity, and the greatest diversity and dominance of Orbicella annularis and Orbicella faveolata. These two species determined the structure and diversity of corals in the central and southern zones of the nsMBRS and their bio-construction in these zones is unique in the Caribbean. Their abundance and distribution depended on the reef habitat area, topographic complexity and species richness. Orbicella species complex were crucial for maintaining the biodiversity and bio-construction of the central and southern zones while A. palmata in the northern zones of the nsMBRS.